Plato's Phaedrus - Plato; Hackforth, R. (Reginald), 1887-1957 (Cambridge : Cambridge University Press, 1997)
The dialogue begins with a playful discussion of erotic passion, then extends the theme to consider the nature of inspiration, love and knowledge. The centerpiece is the myth of the charioteer - the famous and moving account of the vision, fall and incarnation of the soul. Professor Hackforth here translates the dialogue for the student and general reader. There is a running commentary on the course of the argument and the meaning of the key Greek terms, and a full intoduction to explain the philosophical background and the place of this work among Plato's writings.
Originally published in 1952.
Title from publisher's bibliographic system (viewed on 26 Sep 2018).
Keywords: elektronické knihy; electronic books; Plato; Love -- Early works to 1800.; Rhetoric, Ancient; Rhetoric -- Early works to 1800.